Knowledge and perception of COVID-19 among medical students in Indonesia: a cross-sectional study - Nyoman Yudi Antara; Yeni Indriyani; Rina SE Sitindaon; Muslimin; Rima Ernia (Science Midwifery, 2022)
The COVID-19 pandemic is still a major health problem in Indonesia. This is inseparable from the level of knowledge and public perception regarding COVID-19. For this reason, this study aims to examine the level of knowledge and perceptions among the Indonesian people (health students). This descriptive research used a questionnaire created using Google Forms and distributed using social media platforms, such as WhatsApp and Facebook. Most respondents knew the information related to COVID-19 from social media (60.5%). As regards knowledge associated with COVID-19, most respondents were well known about the transmission (99.6%), the incubation period (93.9%), and prevention (89.5%). The perception correctly answered was wearing masks to avoid infection (91.9%), whereas the wrong one was receiving packages from abroad (72.9%). This study conclude that the level of student knowledge varied according to the type of question and the information received. Meanwhile, most of them got information from social media.